Analisis Kesulitan Menerjemahkan al-Qur’an terhadap Penguasaan Kosakata Bahasa Arab di MA Sejahtera - Tahir Tahir; Taufikhidayat Taufikhidayat; Teguh Kurniawan; Nur Syamsiah; Fadlan Fadlan (Departement of Mathematics Education, 2024)
The teaching and learning process is a very important activity and supports the development of both students and educators. Often found in learning are obstacles that become inhibiting factors in achieving learning goals. Learning Arabic is also the same, there are many obstacles that cause learning not to be optimal and even failure. The factors that cause this vary, they can come from internal or internal factors or external or external factors.This research includes qualitative descriptive research, which is research aimed at describing existing phenomena, which are taking place now or in the past. This research uses stages of library research and field research, as well as using interview techniques and documentary data collection which then analyzes the data using qualitative analysis.Based on the research results, several problems were found, including the following: (1) internal factors influenced by laziness and difficulty in memorizing. The second factor, (2) external factors are mostly influenced by the misuse of cellphones.